The longitudinal relationship between executive dysfunction and reactive and proactive aggression in adolescents: impulsivity as a mediator and sex differences - Su, Xiaojie; Li, Wenjie; Hu, Changsheng; Liu, Huimin; Lian, Rong (Frontiers in Psychiatry, 2024)
BackgroundAdolescent aggression poses a significant threat to mental health and social functioning. This study investigated the underlying mechanisms of reactive and proactive aggression in Chinese adolescents, focusing on the roles of executive dysfunction, impulsivity, and sex. We hypothesized that executive dysfunction would predict both reactive and proactive aggression, with impulsivity mediating these relationships. Furthermore, we explored the moderating role of sex in the association between impulsivity and both types of aggression.MethodA longitudinal design with a 1-year follow-up was employed. The sample comprised 617 middle school students (mean age = 15.26 years at Time 2; 59% male). Participants completed self-report questionnaires at two time points (T1: April 2023; T2: April 2024): the Reactive-Proactive Aggression Questionnaire (RPQ), the Teenage Executive Functioning Inventory (TEXI), and the Barratt Impulsiveness Scale (BIS).ResultsExecutive dysfunction at T1 significantly predicted both proactive and reactive aggression at T2. Impulsivity at T2 partially mediated the relationship between executive dysfunction at T1 and both proactive and reactive aggression at T2. Sex moderated the relationship between impulsivity and aggression. Specifically, impulsivity at T2 significantly predicted proactive aggression at T2 only in male adolescents. Impulsivity at T2 significantly predicted reactive aggression at T2 in both male and female adolescents, with a stronger effect observed in males.ConclusionOur findings suggest that executive dysfunction contributes to adolescent aggression both directly and indirectly through increased impulsivity. Sex plays a moderating role, with male adolescents demonstrating greater vulnerability to the influence of impulsivity on aggression. These results underscore the importance of considering executive function, impulsivity, and sex in the development of interventions to prevent and reduce adolescent aggression.